Tinjauan Hukum Islam Terhadap Penerapan Hukum Waris Adat Di Desa Margajaya Kecamatan Lemahsugih Kabupaten Majalengka - Devi Nurmilasari; Yoyo Hambali (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
The application of inheritance law in the indigenous people of Margajaya, Lemahsugih Subdistrict,Majalengka Regency, which basically still adheres to the customs and traditions that they follow fromtheir ancestors. The inheritance system used in Margajaya customary inheritance uses the Parentalsystem, in which the father and mother are equally strong, in terms of distribution and application ofinheritance to the Margajaya customarycommunity. This type of research is Field Research, and themethod uses the Mix Methods method. Namely a research method by combining qualitative researchmethods with quantitative research in a research activity, so that more comprehensive, valid, reliableand objective data will be obtained. The data used in this study are primary data obtained frominterviews and documentation while secondary data is obtained from Liberal Research. The samplestaken in this study were the followers of Packu, Akur and Segendong Sepikul, while for the populationthey were more inclined towards the customary tradition, namely Akur. In data collection techniques,researchers used interview data, observation and documentation. And for the Data Analysis Techniquein its stages, observation, editing, classification, re-verification, analysis and drawing conclusions.The results of the study found that indigenous wans in Margajaya village are using parental customarylaw which is only focused on children and adopted children. The share of the heir’s parents only as agift for his parents, is not included in the wansan. The distribution of the wansan property was oftenpostponed by reason of using the children until they got married. The factor behind the occurrenceof this interview is the lack of knowledge of Islamic legal rights. The implementation of the law thatoccurs in Margajaya village, when viewed from Islamic law, is basically not in accordance withIslamic law. Things like this are considered normal and common in Margajaya society because it is atradition from generation to generation and their ancestors. The custom that is used by the communityin the distribution of inheritance cannot be used as a legal benchmark because it is against Nash, eventhough the purpose of an inheritance is carried out in accordance with Maqasıd Al Syan ah, namelyjustice, it is still not acceptable to Islam